2019
DOI: 10.1177/0021998319871351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silane treatment on the dielectric properties of pineapple leaf/kenaf fiber reinforced phenolic composites

Abstract: This work deals with the dielectric properties of silane treated pineapple leaf fiber and kenaf fiber reinforced phenolic hybrid composites. The aim of the present paper is to investigate the effect of silane treatment on the pineapple leaf fiber–kenaf fiber/matrix interfacial adhesion using the dielectric relaxation spectroscopy in the frequency range from 0.1 Hz to 1 MHz and temperature range from 50 to 180℃. Our hybrid composites were fabricated by hand lay-up method at 50% total fiber loading. All the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A slight increase in the permittivity is noticed after the addition of Cloisite 20A and especially for the temperatures above the T g , indicating a rise of the F I G U R E 5 Isochronal variations of the real (A) and imaginary (B) and isothermal variations of the real (C) and imaginary (D) parts of the complex permittivity for the nanocomposite PP2% [Color figure can be viewed at wileyonlinelibrary.com] material polarizability. [21,23,24] Two peaks are clearer, in the curves of variations of ε 00 indicating the presence of two different phenomena. The first peak in the same frequency domain as the PP matrix (≈ 1 Hz-10 3 Hz), is attributed to the α c relaxation.…”
Section: Analysis Of Different Relaxation Phenomenamentioning
confidence: 95%
See 1 more Smart Citation
“…A slight increase in the permittivity is noticed after the addition of Cloisite 20A and especially for the temperatures above the T g , indicating a rise of the F I G U R E 5 Isochronal variations of the real (A) and imaginary (B) and isothermal variations of the real (C) and imaginary (D) parts of the complex permittivity for the nanocomposite PP2% [Color figure can be viewed at wileyonlinelibrary.com] material polarizability. [21,23,24] Two peaks are clearer, in the curves of variations of ε 00 indicating the presence of two different phenomena. The first peak in the same frequency domain as the PP matrix (≈ 1 Hz-10 3 Hz), is attributed to the α c relaxation.…”
Section: Analysis Of Different Relaxation Phenomenamentioning
confidence: 95%
“…Such process arises from the polarization of induced dipoles created, due to the trapped charge carriers, at the interfaces between the Cloisite 20A and PP matrix. [21,23,24] These two relaxation phenomena are thermally activated and move towards high frequencies when increasing temperature.…”
Section: Analysis Of Different Relaxation Phenomenamentioning
confidence: 99%
“…The advantage of these reinforcements lies in particular in their good specific properties: biodegradability, abundance, renewable nature, and low cost. [ 1–6 ] Several natural fibers have been proposed as a substitute for conventional synthetic fibers including hemp, flax, jute (in Europe), date palm, alfa (in Africa) or even pineapple leaf (PALF), kenaf (KF), and Oil Palm Empty Fruit Bunch (OPEFB) (in Asia). Currently, Malaysia produces around 17 million tons of OPEFB fibers as waste [ 7, 8 ] and are used in the polymer composite industries for different applications.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Recent studies have shown that hybridization of natural fibers with synthetic or other natural fibers can improve the physical properties of polymeric matrix composites according to the desired industrial requirements. [12][13][14][15][16][17] More recently, many works have been carried out on the hybridization of KF fibers with natural and/or synthetic nanofillers such as KF/jute fibers/E-glass, [18] KF/coir fibers/ MMT, [19] KF/PALF fibers, [5] KF/hemp/flax/glass fibers, [20] and Areca fiber-reinforced nano-silica and neem oiltoughened epoxy resin biocomposites. [21] For example, studies on the mass change, thermal decomposition, and thermal stability of woven glass/KF/epoxy hybrid composite filled with clay nanoparticles in small quantities were studied by Mazlan et al [22] Such hybridization demonstrated better interfacial adhesion between the treated KF and the epoxy.…”
Section: Introductionmentioning
confidence: 99%
“…Natural composite properties were improved by hybridization using fibers, filler incorporation and coupling agents. [6][7][8][9][10] The addition of 35% pineapple leaf fiber (PALF) enhanced the tensile and flexural properties of polyester-based composites with 3 mm fiber length and 17 MPa compression pressure. 11 Pineapple fiber using NaOH treatment showed effective tensile strength results than the KOH treatment.…”
Section: Introductionmentioning
confidence: 99%